2018
DOI: 10.1055/a-0677-170
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new pan-enteric video capsule endoscopy system in patients with suspected or established inflammatory bowel disease – feasibility study

Abstract: Background and study aims  Inflammatory bowel disease (IBD) affects the small bowel and colon. Endoscopic evaluation of these organs is essential. The new pan-enteric Crohn’s capsule (PCC) system is customized for complete coverage of IBD lesions in the entire bowel, allowing assessment and follow-up of disease severity and extent. The aim of this study was to evaluate the functionality of the PCC system in patients with suspected or established IBD. Patients and methods  This was a prospective five-center fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 18 publications
4
55
0
Order By: Relevance
“…This proof of concept pilot multi-center study carried out in routine clinical practice confirms that the novel PillCam™ Crohn's system is safe and provides high technical and endoscopic performances for CD assessment [12,14]. Our results also suggest that the panoramic 344°-view clearly improves small-bowel capsule visualisation, thus potentially improving both diagnostic accuracy and clinical management for patients undergoing small bowel CE for suspected or established CD.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…This proof of concept pilot multi-center study carried out in routine clinical practice confirms that the novel PillCam™ Crohn's system is safe and provides high technical and endoscopic performances for CD assessment [12,14]. Our results also suggest that the panoramic 344°-view clearly improves small-bowel capsule visualisation, thus potentially improving both diagnostic accuracy and clinical management for patients undergoing small bowel CE for suspected or established CD.…”
Section: Discussionsupporting
confidence: 70%
“…A recent pilot study has suggested that PCS would possibly result in higher diagnostic yields than ileo-colonoscopy in patients with known a New diagnosis of CD was defined for relevant CE findings strongly supporting a definite diagnosis following a 6-months follow-up active CD following a capsule colon cleansing protocol [12]. PCS showed to be safe and to enable the direct evaluation of the entire gut based on the preliminary data from a proof-of-concept feasibility study conducted on CD and ulcerative colitis patients [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[157][158][159][160][161][162] The advent of capsule devices with a prolonged operating time has recently opened the era of pan-intestinal CE. 159,162 This all-in-one and on-demand approach has a promising application in IBD 159,[162][163][164][165] where it can supposedly speed up the diagnostic work-up and decrease the need for endoscopic procedures. However, the evidence so far collected on this novel approach is very limited.…”
Section: Capsule Enteroscopymentioning
confidence: 99%